The Effect of Social Media Marketing and Electronic Word of Mouth Through Instagram on Purchasing Decisions for Hanasui Products - Siti Marwa; Miftahul Jannah (Eco-Entrepreneur, 2026)
Purpose: This study aims to analyze the effects of social media marketing and electronic word of mouth (e-WOM) on purchasing decisions for Hanasui products.Design/methodology/approach: A quantitative approach was employed using purposive sampling. The sample consisted of 100 Hanasui consumers aged at least 17 years who use Instagram, have visited the Hanasui Instagram account, and have purchased Hanasui products at least once. Data were collected through questionnaires distributed via Google Forms using a five-point Likert scale and analyzed using multiple linear regression with SPSS version 27.Findings: The results show that social media marketing has a positive but insignificant effect on purchasing decisions. In contrast, e-WOM has a positive and significant effect, indicating that consumer reviews and recommendations play a more important role in influencing purchases. Simultaneously, social media marketing and e-WOM significantly affect purchasing decisions.Research limitations/implications: The study is limited to Hanasui consumers and a sample of 100 respondents. Future research should involve larger samples and additional variables.Practical implications: Companies should focus on encouraging positive e-WOM to strengthen consumer purchasing decisions.Originality/value: This study provides empirical evidence on the relative influence of social media marketing and e-WOM on cosmetic product purchasing decisions in Indonesia.